Room temperature ferromagnetism in polymorphic (Cr,Mn)Te films - Mihyeon Kim; Ryoga Nakajima; Takashi Harumoto; Yi Shuang; Daisuke Ando; Nobuki Tezuka; Yuta Saito; Yuji Sutou (APL Materials)
This study demonstrates the first investigation of sputtered polymorphic Cr–Mn–Te ternary films, which hold promise for spintronic and magnetic semiconductor applications, focusing on their magnetic properties. Notably, ferromagnetism, which was initially absent in the as-deposited Cr0.17Mn0.34Te0.49 [(Cr,Mn)Te] films, was observed with increasing annealing temperature and persisted despite the polymorphic change from the wurtzite-type structure (β-phase) to a stable NiAs-type structure (α-phase) by x-ray diffraction measurement and transmission electron microscopy observation. We demonstrated that the (Cr,Mn)Te film exhibited a unique polymorphic change, which was characterized by multiple electrical resistance states. Magnetic measurements revealed that the low-resistance phases of β-(Cr,Mn)Te and α-(Cr,Mn)Te films exhibited ferromagnetic behavior at room temperature, with Curie temperatures of 367 and 389 K, respectively. The emergence of ferromagnetism might be attributed to Cr incorporation, resulting in the generation of defects in the Mn–Te lattice. These pioneering findings highlight the potential of Cr-incorporated films, which combine magnetic and semiconducting properties, for applications in energy-efficient information processing.